Effectiveness of Teachers’ Training in Assessment Techniques: Participants’ Perception. - Baral, N; Gautam, A; Lamsal, M; Paudel, B H; Lal Das, B K; Aryal, M (Kathmandu University Medical Journal, 2012)
Background Medical education has experienced a rapidly changing scenario especially during the past three decades. Teachers’ training programs have emerged in recent years as a more in depth and comprehensive mechanisms for strengthening instructional skills and formulating assessment techniques among faculty members. Objective The present study was carried out with the aim of assessing effectiveness of teacher’s training workshop on assessment techniques at B.P. Koirala Institute of Health sciences (BPKIHS), Dharan, Nepal. Methods: In this prospective questionnaire based study, the 26 entry level teachers were enrolled. They were requested to fill the questionnaire before and after the workshop on the assessment techniques at BPKIHS, Dharan. Methods Twenty six teachers majority of whom were entry level teachers comprising of medical, dental, nursing and allied sciences participated in pre- and post test analysis on the various components of written and oral examinations. A two and half days long training was conducted having 9 hours of teaching interactive sessions, 6 hours of group exercises, daily evaluation and 3 hours of presentation by participants. There was high degree of agreement with most topics of the assessment training. Results There was a significant gain in knowledge (p< 0.001) by the participants. All the participants (100%) agreed upon the training being informative and learned new things about assessment. More practice session with longer duration with invited resource persons were also suggested for an effective session. Conclusion Thereis an immense opportunity for a better and comprehensive training in evaluation techniques in medical education..DOI: http://dx.doi.org/10.3126/kumj.v9i3.6303 Kathmandu Univ Med J 2011;9(3):189-92